Evaluation of the project program for strengthening the Pancasila student profile in Madrasah Ibtidaiyah - Amin, Muhammad (Mitra PGMI: Jurnal Kependidikan MI, 2025)
The purpose of this study is to evaluate the Pancasila student profile strengthening project at Madrasah Ibtidaiyah. This research employs a mixed-method approach with the CIPP (Context, Input, Process, Product) evaluation model. Data collection techniques used in this study include interviews, observations, documentation, and questionnaires. The research subjects consist of madrasah heads, class teachers, and students. The objects of this study are Madrasah Ibtidaiyah Al-Bukhori Pekanbaru, Madrasah Ibtidaiyah Al-Birra Pekanbaru, and Madrasah Ibtidaiyah Tahfidz Cendekia Pekanbaru. The data analysis techniques used in this study are data reduction, data presentation, and verification/conclusion. The results of the study indicate that the implementation of the Pancasila Student Profile Strengthening Project (P5) learning using the CIPP model at the Pekanbaru City Elementary Madrasah is still in the less-than-good category and requires various improvements. These improvements are mainly needed at three main stages, namely input, process, and product. At the input stage, aspects that require attention include P5 learning resources, the availability of human resources that support P5 learning, and the P5 learning planning flow. At the process stage, improvements are needed in implementing P5 learning. Meanwhile, at the product stage, the learning outcomes of P5 learning also require improvement.